El rol del sistema financiero en el desarrollo sostenible en los años 2002-2016: economías emergentes y desarrolladas - Olulo Taipe, Kaori Stefania (2020)
We currently know that financial systems play a very important role in the economic growth of countries. But it can also play a role in sustainable development as will be analyzed in this work. Sustainable development is made up of 3 pillars: economic development, social development, and protection of the environment. It will be evaluated how the financial system, consisted of the banking sector and the stock market for this analysis, has or does not have a positive or negative impact on each pillar. Therefore, the purpose of this research is to find out if the Financial System meets or has the potential to help achieve the main objectives of Sustainable Development in emerging economies and developed economies, which is to end poverty, protect the planet and ensure that all people enjoy peace and prosperity. The objectives of this research are: 1) Define sustainable development and expose its importance in the world economy, 2) Identify the most important financial institutions and their actions that promote sustainable development, and 3) estimate whether the granting of credit and the Financing through the capital market promotes sustainable development. For the third objective, an empirical analysis was performed using econometric tools. Panel data will be used, and three models are estimated for each pillar of sustainable development by applying panel data with generalized least squares. Various results are obtained from the models. It is shown that the impact that the financial system can have is not very great, but there is an impact. The expected results are obtained for the models of social development and protection of the environment. In the case of economic development, only the expected results are obtained for the stock market. In conclusion, with this study, we observed there is an impact of the Financial System on sustainable development for emerging economies and developed economies. Even this impact is not large enough to be the most relevant factor in promoting sustainable development, but it does have potential. The impact must continue to be studied in order to create adequate policies that help achieve the Sustainable Development Goals.